Показники дисфункції ендотелію у хворих на хронічну критичну ішемію нижніх кінцівок = Endothelial dysfunction indicators in patients with chronic critical limb ischemia - Goni, S. K.T. (Journal of Education, Health and Sport, 2016)
Goni S.-K.T. Показники дисфункції ендотелію у хворих на хронічну критичну ішемію нижніх кінцівок = Endothelial dysfunction indicators in patients with chronic critical limb ischemia Journal of Education, Health and Sport. 2016;6(10):485-492. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.165834 http://ojs.ukw.edu.pl/index.php/johs/article/view/3982 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. УДК: 617.58-005.04-036.12-089 ПОКАЗНИКИ ДИСФУНКЦІЇ ЕНДОТЕЛІЮ У ХВОРИХ НА ХРОНІЧНУ КРИТИЧНУ ІШЕМІЮ НИЖНІХ КІНЦІВОК С.-К.Т. Гоні Харківський національний медичний університет Кафедра хірургії №2, Харків Резюме В статті оцінені рівні прямих та опосередкованих показників ендотеліальної дисфункції (ендотелін-1, VEGF, фібриногену та С-реактивний білок) у 29 хворих на хронічну критичну ішемію нижніх кінцівок з дистальною формою ураження судинного русла у віці від 59 до 84 років. Хворі були обох статей, з них 12 (41,4%) - хворі на облітеруючий атеросклероз та ЦД. Показано, що незалежно від стадії ішемії та наявності ЦД, у хворих, що досліджувалися, виявлено порушення вазомоторної функції ендотелію (за даними рівня ендотелін-1), підвищення проліфераційної активності ендотелію (за даними рівня VEGF), порушення гемостатичної (за даними рівня фібріногену) та прозапальної функції ендотелію (за даними рівня С-реактивного білку) Ключові слова: критична ішемія нижніх кінцівок, ендотеліальна дисфункція, ендотелін-1, васкулоендотеліальний фактор росту, фібриноген, С-реактивний білок ENDOTHELIAL DYSFUNCTION INDICATORS IN PATIENTS WITH CHRONIC CRITICAL LIMB ISCHEMIA S.-K.T. Goni Kharkiv National Medical University, Ministry of Health of Ukraine , Department of Surgery № 2 Abstract This article shows the results of determination of levels of direct and indirect indicators of endothelial dysfunction (ET1, VEGF, fibrinogen and CRP) in 29 patients with chronic critical limb ischemia with distal type of lesion of the vascular bed, aged from 59 to 84 years. Patients were of both sexes, of which 12 (41.4%) - patients with atherosclerosis and diabetes. It is shown that regardless of the stage of ischemia and the presence of diabetes in patients who were investigated, breach of vasomotor endothelial function (according to the level of endothelin-1), increased proliferative activity of endothelium (according to the level of VEGF), a violation of hemostatic (according to the level of fibrinogen) and proinflammatory endothelial function (based on C-reactive protein) was shown. Keywords: сritical limb ischemia, endothelial dysfunction, endothelin-1, VEGF, fibrinogen, C-reactive protein